Modifying bone mineral density, physical function, and quality of life in children with acute lymphoblastic leukemia. Issue 4 (29th December 2017) - Cox, Cheryl L.; Zhu, Liang; Kaste, Sue C.; Srivastava, Kumar; Barnes, Linda; Nathan, Paul C.; Wells, Robert J.; Ness, Kirsten K.
Abstract: Background: The early effects of childhood acute lymphoblastic leukemia (ALL) include decreased physical function, bone mineral density (BMD/g/cm 2 ), and health‐related quality of life (HRQL). We assessed the capacity of a physical therapy and motivation‐based intervention, beginning after diagnosis and continuing through the end of treatment, to positively modify these factors. Procedure: A 2.5‐year randomized controlled trial of 73 patients aged 4–18.99 years within 10 days of ALL diagnosis assessed BMD at baseline (T 0 ) and end of therapy (T 3 ), strength, range of motion, endurance, motor skills, and HRQL at baseline (T 0 ), 8 (T 1 ), 15 (T 2 ), and 135 (T 3 ) weeks. Results: There were no significant changes between groups (intervention, n = 33; usual care, n = 40) in BMD ( P = 0.059) at T 3 or physical function and HRQL at T 0 –T 3 . While BMD declined in both the intervention (T 0 = −0.21, T 3 = −0.55) and usual care (T 0 = −0.62, T 3 = −0.78) groups, rates of decline did not differ between groups ( P = 0.56). Univariate analysis (n = 73) showed associations of higher T 3 bone density with body mass index T 1 ( P = 0.01), T 2 ( P = <0.0001), T 3 ( P = 0.01), T 3 ankle flexibility/strength ( P = 0.001), and T 2 parent ( P = 0.02)/T 0 child ( P = 0.03) perceptions of less bodily pain. Conclusions: The intervention delivered during treatment was not successful in modifying BMD, physical function, or HRQL. Physical activity, at the level and intensity required to modify these factors, may not be feasible during early treatment owing to the child's responses to the disease and treatment. Future studies will consider intervention implementation during late maintenance therapy, extending into survivorship.